(untitled) (Journal of Hama University, 2022)
Purpose of the study: The purpose of this study was to evaluate fracture strength of veneered zirconium dioxide crowns designed with different incisal porcelain thicknesses. Materials and Methods: With a standardized technique, thirty bi-layered Zirconia crowns divided into three groups of 10 were used in this study. Groups were divided according to different thicknesses of incisal porcelain veneer on zirconium dioxide cores of equal thickness (0.5mm). Porcelain thicknesses were 1.5, 1.0 and 0.5mm. Crowns were loaded to fracture. Data were statistically analyzed. Results: Means of failure loads were 1368.90N for 0.5mm group, 1432.11N for 1.0 mm group and 957.11N for 1.5mm group. There was no significant difference (p>0.05) in fracture loads between groups 1.0 and 0.5mm, whereas the 1.5mm group showed significantly lower fracture loads in comparison with the other two groups Conclusions: changes in the thickness of the incisal porcelain layer have a significant influence on fracture strength of veneered zirconium dioxide crowns.